2020
DOI: 10.3390/app10248897
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Transformer Oil Contamination from the OLTC Gases in the Power Transformers of a Distribution System Operator

Abstract: Power transformers are considered to be the most important assets in power substations. Thus, their maintenance is important to ensure the reliability of the power transmission and distribution system. One of the most commonly used methods for managing the maintenance and establishing the health status of power transformers is dissolved gas analysis (DGA). The presence of acetylene in the DGA results may indicate arcing or high-temperature thermal faults in the transformer. In old transformers with an on-load … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Faults pointed out by the various existing methods can have different origins, giving rise to different failures. Based on [39,40,41], Table 2 summarizes at a macro level the four major types of failures detected by analyzing the gases dissolved in the oil and potential reasons for them. However, to determine the source of a failure with accuracy, it is essential to Metallic particles in the oil X X…”
Section: Traditional Diagnostic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Faults pointed out by the various existing methods can have different origins, giving rise to different failures. Based on [39,40,41], Table 2 summarizes at a macro level the four major types of failures detected by analyzing the gases dissolved in the oil and potential reasons for them. However, to determine the source of a failure with accuracy, it is essential to Metallic particles in the oil X X…”
Section: Traditional Diagnostic Methodsmentioning
confidence: 99%
“…Major failures in large power transformers with signature detected by analyzing the gases dissolved in the oil[39,40, 41].…”
mentioning
confidence: 99%
“…The tank contains the oil and provides physical protection and support for the different components of the transformer, besides ensuring the grounding of the magnetic circuit and the various metal parts. The tank may show cracks [38], essentially resulting from environmental wear and tear, such as those resulting from corrosive environments, high humidity, vibrations, and solar radiation. The tank walls may also rupture due to high-pressure gases resulting from internal arcs that vaporize the oil [39].…”
Section: Tankmentioning
confidence: 99%
“…In terms of metal occurrence distribution, Fe and Zn have similar occurrence distribution laws (see Figures 4b and 4d), and the concentration of different occurrence follows the order of F1 > F2 > F3. However, the content of different occurrence of Cu is opposite to that of Fe or Zn, showing a trend of F1 < F2 < F3, which may be related to the accelerated aging process of oil products and the participation of copper in complex reactions [14][15][16]. Previous studies have shown that oxidation products in the aging process of transformer oil and insulating paper [17][18][19], such as various organic acids, alcohols and aldehydes will undergo polymerization, condensation and other reactions, resulting in a large number of asphaltene, resin and other high molecular polymers reacting with Cu [20], which in turn cause an increase in the content of organic extractable copper (F3).…”
Section: Distribution Of Occurrence Of Metals In Normal Transformer Oilmentioning
confidence: 99%